A new approach for composite coating development on duplex stainless steel (DSS) - Paijan, Lailatul Harina; Maleque, Md. Abdul (2019)
Duplex stainless steel (DSS) have gained increasing interest in recent years for a number of applications to the components of injection system pumps, compressor and valves in the oil and gas sector; pumps, shafts and agitator blade in chemical sectors; components of injection pipe and centrifugal fans in power generation and piston rings and cylinder liners in automotive sectors that require a good combination of hardness and wear resistance of DSS. However, this material has experienced tribological problem in the service. Therefore, the present invention was aimed for the new development of surface modification for DSS to explore the possibility of producing a new method of composite coated DSS using individual TIG torch melting technique and low temperature gaseous nitriding processes, respectively. The characterization of composite coated was performed using scanning electron microscopy (SEM), energy dispersive spectrometry (EDS) and x-ray diffraction (XRD) analyzer. The morphologies of composite coated showed a good metallurgical bonding and uniform distribution of the SiC and expanded austenite with the existence of intermetallic compound. Furthermore, this composite coated can be used as an efficient solid lubricant for tribological application. This composite coated is expected to show better hardness and tribological behavior with the metallic matrix as well as excellent thermal stability. The new composite coated provides more durable surface than substrate material and improve surface life (reduce maintenance and increase lifespan of the material). All these reasons serve as the main thrust of this invention project. The optimum processing conditions on the hard layer quality certainly could help and attract industry to develop hard layer method in order to suit the relevant applications. Moreover, this concept can produce hard coating of significant thickness in the large surfaces as well as localized area. It is highly considered that performing this process can produce in novelty for hard surface layer and is uniquely applied to DSS in improving the surface properties.